Individual Monitoring of Behavior to Enhance Productivity and Welfare of Animals in Small-Scale Intensive Cattle Grazing Systems - Anzai, Hiroki; Hirata, Masahiko (Frontiers in Sustainable Food Systems, 2021)
A 1000-word abstract was sent separately according to the workshop's submission rules.